Structural change and global trade - Logan T. Lewis; Ryan Monarch; Michael Sposi; Jing Zhang (Federal Reserve Bank of Chicago, 2020)
Services, which are less traded than goods, rose from 58 percent of world expenditure in 1970 to 79 percent in 2015. Using a Ricardian trade model incorporating endogenous structural change, we quantify how this substantial shift in consumption has affected trade. Without structural change, we find that the world trade to GDP ratio would be 15 percentage points higher by 2015, about half the boost delivered from declining trade costs. In addition, this structural change has lowered the global welfare gains from trade integration by almost 40 percent over the past four decades. Absent further reductions in trade costs, ongoing structural change implies that world trade as a share of GDP would eventually decline. Going forward, higher income countries gain relatively more from reducing services trade costs than from reducing goods trade costs.
Keywords: F41; L16; O41; 330; Globalization; Structural Change; International Trade